Study the Efficacy of Mono and Combination Therapy of Amoxicillin and Levofloxacin against S.aureus causing Respiratory Tract Infection in Rabbits - Abdulwahhab Abed Khalifa; Ahmad Najim Abed salih (Diyala Journal for Veterinary Sciences, 2024)
This study was conducted to investigate the difference between the effect of monotherapy by amoxicillin and levofloxacin with their combination in treating respiratory infection induced by Staphylococcus aureus in rabbits. For this purpose the study was divided into two parts, in vitro and in vivo. The in vitro included: determination of minimum inhibitory concentration (MIC), inhibition zone, interaction between amoxicillin and levofloxacin. The results of in vitro study showed that the MIC was 64 μg/ml, 8μg/ml and 64μg/ml+8μg/ml for amoxicillin and levofloxacin and their combination respectively. The inhibition zone produced by 0.5MIC, 1MIC and 2MIC of amoxicillin, levofloxacin and their combination was concentration dependent, which were 8.66±0.33mm, 14.66±0.16mm and 11.33±0.33mm for amoxicillin, levofloxacin and their combination respectively by using 1MIC. The in vivo study included 25 rabbits, five animals kept as negative control without any infection or treatment while the remaining 20 animals were infected with S.aureus to induce respiratory tract infection and then divided into four equal groups, first one without treatment (positive control), second and third groups treated with amoxicillin 28.75mg/kg and levofloxacin 24.17mg/kg respectively while the last one treated with combination of half doses of amoxicillin and levofloxacin. In general, the results showed that the levofloxacin was the best in decreasing the deleterious effect produced by S.aureus infection followed by combination then amoxicillin, levofloxacin was the superior in decreasing the severity of clinical signs improves the blood picture represented by decreasing theinflammatory cells like white blood cell and keeping the red blood cells within normal range. In conclusion, treatment the respiratory tract infection with mono therapy by levofloxacin was better than use it in combination with amoxicillin.